KARAKTER PEMIMPIN MELAYU DALAM PEMIMPIN UNGKAPAN MELAYU KARYA TENAS EFFENDY - Fera Andriani; Elmustian Rahman; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the characters in the text Leader Leader Malay Malay phrase Tenas work Effendy. This study used a qualitative approach and descriptive method that aims to describe the characters contained in the text of the Malay phrase Leaders Work Tenas Effendy. In this study the authors used data collection techniques are engineering documentation, then classified based on the character-karakater leader according to Islam formulated into conclusions. The results of the research I have found in this study is the leader according to Islamic code contained in the text leader among Malay expression trustful character, character fathanah, characters and character shidiq sermons.Keywords: Character, leader of Islamic, Malay leaders, Malay teaching point.